Etika Penggunaan Prompt Kecerdasan Buatan (AI) dalam Memelihara Kesahihan Pegangan Ahli Sunnah Wal Jamaah dalam Akidah, Fikah dan Tasawuf: Ethical Use of Prompts in Artificial Intelligence (AI) to Safeguard the School of Thought of Ahl Sunnah Wal Jamaah (ASWJ) in Creed, Fiqh and Tasawwuf - Muhammad, Manar; Sapuan, Muhammad Zaki; Jani, Muhammad Haziq (Jurnal Usuluddin, 2025)
The rising utilisation of artificial intelligence (AI) in everyday life, including within Islamic religious discourse, has raised concerns regarding the potential dissemination of deviant ideologies through unfiltered AI generated responses. In response to this issue, the present study aims to examine the necessity of employing ethically framed prompts in AI systems to enhance the awareness of Muslim users, particularly in preserving the doctrinal integrity of Ahl al-Sunnah wa al-Jamaah (ASWJ) school of thought in the domains of ʿaqidah (theology), fiqh (jurisprudence), and tasawwuf (spirituality). This qualitative study adopts a content analysis approach, examining ChatGPT’s responses to a range of prompt designs, some of which explicitly articulate the theological and legal frameworks of Islam, while others remain general. The data are analysed comparatively with reference to authoritative ASWJ sources and current literature on AI ethics. The findings indicate that ambiguous or unspecific prompts may result in the integration of ideological elements that deviate from ASWJ orthodoxy. Conversely, precise and contextually guided prompts tend to produce responses that are more consistent with theologically sound. The study introduces the concept of the ‘Ethical Islamic Prompt’ as a foundational framework for guiding Muslim engagement with AI systems. The implications of this study contribute to the early development of Islamic AI literacy and offer a basis for formulating ethical AI usage policies within religious authorities and Islamic educational institutions.